Assessment of the Severity of Disease in Patients with Bronchial Asthma, Before and After Yoga: A Randomised Trial - Candy Sodhi; Amit Bery; Sheena Singh (Open Journal of Asthma - Peertechz Publications, 2018)
Introduction: Asthma is a common chronic inflammatory disorder affecting about 300 million people worldwide. As a holistic therapy, yoga has the potential to relieve both the physical and psychological suffering of people with asthma, and its popularity has expanded globally. Yoga includes several techniques: physical postures (asanas), voluntarily regulated breathing (pranayama) and meditation. Materials and Methods: Sixty patients with bronchial asthma underwent training for eight weeks in an integrated set of yoga exercises, including breathing exercises, suryanamaskar, yogasana (physical postures), pranayama (breath slowing techniques), dhyana (meditation) and were told to practice these exercises for 65 minutes daily. They were then compared with a control group of sixty patients with asthma matched for age, sex, and type and severity of asthma, who continued to take their usual drugs. Their daily records were used to assess the number and severity of attacks and the medication used by them. Apart from that, Group A patients also kept a record of the Yogic Exercises performed by them twice daily.